Oxytocin ameliorates skin damage and oxidant gastric injury in rats with thermal trauma - YEGEN, BERRAK; ERZİK, CAN (ELSEVIER SCI LTD, 2008)
Transient splanchnic vasoconstriction following major burns causes oxidative and/or nitrosative damage in gastrointestinal tissues due to ischemia, which is followed by reperfusion injury. Oxytocin (OT), a hypothalamic nonapeptide, possesses antisecretory and antiulcer effects, facilitates wound healing and is involved in immune and inflammatory processes. To assess the possible protective effect of oxytocin (OT) against burn-induced gastric injury, Sprague-Dawley rats (250-300 g) were randomly divided into three groups as control (n = 8), OT-treated burn (n = 8) and saline-treated burn (n = 8) groups. Under anesthesia, the shaved dorsal skin of rats was exposed to 90 degrees C water for 10 s to induce burn injury covering 30% of total body surface area in a standardized manner. Either oxytocin (5 mu g/kg) or saline was administered subcutaneously immediately after and at 24 h following burn, and the rats were decapitated at 48 h. Serum samples were assayed for TNF-alpha, and stomach was taken for the determination of malondialdehyde (MDA), myeloperoxidase (MPO) activity, DNA fragmentation rate (%) and histopathological examination. MDA and MPO were assayed for products of lipid peroxidation and as an index of tissue neutrophil infiltration, respectively. When compared to control group, burn caused significant increases in gastric MDA and MPO activity and increased microscopic damage scores at 48 h (p < 0.001). Oxytocin treatment reversed the burn-induced elevations in MDA and MPO levels and reduced the gastric damage scores (p < 0.001, p < 0.01), while TNF-alpha levels, which were increased significantly at 48th h after injury (p < 0.001), were abolished with OT treatment (p < 0.001). The results of this study suggest that oxytocin may provide a therapeutic benefit in diminishing burn-induced gastric inflammation by depressing tissue neutrophil infiltration and decreasing the release of inflammatory cytokines, but requires further investigation as a potential therapeutic agent in ameliorating the systemic effects of severe burn. (C) 2007 Elsevier Ltd and ISBI. All rights reserved.
Keywords: oxytocin; burn; oxidative damage; VASCULAR SMOOTH-MUSCLE; LIPID-PEROXIDATION; INFLAMMATION; STRESS; VASOPRESSIN; RECEPTORS; GROWTH; NEUTROPHILS; EXPRESSION; INCREASES